Islamic Microfinance: Challenges and Development - Nur Indah Riwajanti (Jur. Akuntansi, Politeknik Negeri Malang, 2015)
AbstractThe purpose of this study are to explore the challenges and development of Islamic microfinance worldwide based on literature survey using thematic approach. The challenges faced by Islamic banking institutions varied by size of organisation and nature of operation. As such, Islamic microfinance, being a small institutions providing micro financing, might face the different challenges. The findings suggest that Islamic microfinance face problems and challenges in terms of Shari'ah compliant issues, lack of products diversification, lack of fund, lack of training and networking, lack of supportive regulation and microfinance strategies, lack of wider outreach as Islamic microfinance mostly concentrated only in some countries. However, despite the above challenges, Islamic microfinance has been grown in some countries providing alternative financing driven by potential demand from both Muslims and non-Muslim market, eg. West Bank, Gaza, Jordan, Algeria, Yemen and Syria. In other parts of the world, Islamic microfinance also has shown promising growth.AbstrakStudi ini bertujuan untuk mengetahui tantangan dan perkembangan keuangan mikro Islam berdasarkan studi literatur dengan pendekatan tematik. Tantangan yang dihadapi oleh lembaga perbankan dan keuangan Islam bervariasi dipengaruhi oleh ukuran organisasi dan gaya operasinya. Oleh karena itu, lembaga keuangan mikro syariah sebagai lembaga yang berukuran kecil, nampaknya menghadapi tantangan yang berbeda. Hasil penelitian menunjukkan bahwa tantangan yang dihadapi oleh keuangan mikro syariah meliputi isu-isu menyangkut keesuaian dengan syariah, kurangnya diversifikasi produk, kekurangan dana, kekurangan pelatihan dan jaringan, kekurangan dukungan daam bentuk peraturan dan strategi lembaga keuangan mikro, kurangnya wilayah cakupan karena lembaga keuangan mikro sangat berkonsentrasi hanya pada beberapa negara di Asia Selatan, dll. Namun di samping menghadapi tantangan tersebut, lembaga keuangan mikro syariah sudah berkembang di beberapa negara dengan memberikan beberapa alternatif pembiayaan didorong oleh potensi permintaan pasar Muslim dan non-Muslim, misalnya Tepi Barat, Gaza, Yordania, Algeria, Yaman dan Syria. Di belahan dunia lain, keuangan mikro Islam juga sudah menunjukkan perkembangan yang menjanjikan.